CUSTOMER RELATIONSHIP MANAGEMENT IN THE LUXURY REAL ESTATE MARKET: A SYSTEMATIC REVIEW - Cristina Constantino da Costa Silva, Amanda (Revista Gênero e Interdisciplinaridade, 2025)
The luxury real estate market is distinguished by a clientele with high purchasing power (High Net Worth Individuals - HNWI) who demand an exceptionally high level of service and relationship management. Customer Relationship Management (CRM) emerges as a fundamental strategic tool to meet these expectations; however, generic CRM practices prove insufficient. This article aims to identify and analyze, through a systematic literature review, the differentiated CRM practices that contribute to the attraction, retention, and loyalty of clients in the luxury real estate market. The methodology follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, encompassing searches in scientific databases and analysis of relevant published articles. The results indicate that the most effective strategies integrate extreme personalization, cutting-edge technology (such as AI and *predictive analytics*), and a strong human component focused on building trust and offering exclusive experiences. The study identifies five critical dimensions for luxury CRM – Relational, Technological, Service, Value, and Organizational – and proposes a conceptual model for its implementation. It concludes that success in the luxury real estate market depends on a transition from a transactional CRM model to a relational model, where discretion, proactivity, and the creation of intangible value are the pillars for building enduring and profitable relationships with high net worth clients.